2020
DOI: 10.3390/diagnostics10050254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Uterine Artery Doppler and Estrogen Milieu in Oocyte Donation Pregnancies—A Pilot Study

Abstract: Oocyte donations (OD) represent 4.5% of all in vitro fertilization (IVF) cycles. While OD pregnancies face increased risks of obstetrical complications, especially pregnancy-induced hypertension and pre-eclampsia (PE), little is known about the physiology and the physiopathology of placentation. We performed a prospective case-control study to analyze uterine artery Doppler pulsatility index (UtA-PI) and serum maternal 17β-estradiol (17β-E) at 11 + 0 to 13 + 6 weeks’ gestation in singleton pregnancies with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Aberrant human lymphocyte antigen (HLA) allogenicity can alter the function of uterine natural killer cells (uNK) and lead to the abnormal maternal blood supply to the placenta, which is the predominant cause of facilitates disorders such as PE and fetal growth restriction [26]. A recent study also showed abnormally low uterine arteries pulsatility index and serum maternal 17 β -E at 11 to 13 + 6 weeks in oocyte donations as compared to natural conceptions [27,28]. The authors of this study described this new phenomenon as increasing placental perfusion to compensate for maternal or placental dysfunction [27].…”
Section: Summary Of Key Resultsmentioning
confidence: 99%
“…Aberrant human lymphocyte antigen (HLA) allogenicity can alter the function of uterine natural killer cells (uNK) and lead to the abnormal maternal blood supply to the placenta, which is the predominant cause of facilitates disorders such as PE and fetal growth restriction [26]. A recent study also showed abnormally low uterine arteries pulsatility index and serum maternal 17 β -E at 11 to 13 + 6 weeks in oocyte donations as compared to natural conceptions [27,28]. The authors of this study described this new phenomenon as increasing placental perfusion to compensate for maternal or placental dysfunction [27].…”
Section: Summary Of Key Resultsmentioning
confidence: 99%
“…Owing to the lack of evidence, this result could be variously explained: first, we could hypothesize that the smaller placental volumes detected in OD placentas could imply a lower estrogen release compared to natural and autologous IVF pregnancies ( Rizzo et al , 2016 ; Mandia et al , 2020 ); and second, we could speculate that oral estrogen administration might inhibit placental production, in a sort of feedback mechanism that is common in many endocrine systems. Undoubtedly, placental function in OD is reduced compared to naturally conceived and autologous IVF pregnancies: as observed by Savasi et al (2015) , first trimester placental markers, such as free β-hCG and PAPP-A, are significantly altered, suggesting a reduced crosstalk at the fetal–maternal interface ( Savasi et al , 2015 ).…”
Section: The Early Stages Of Pregnancymentioning
confidence: 99%
“…A review of the literature has highlighted only a few studies, mainly from our study group. Mandia et al (2020) compared serum E2 levels in four different groups (55 OD pregnancies, 48 autologous fresh IVF/ET pregnancies, 10 autologous FET pregnancies and 122 naturally conceived pregnancies) during the late first trimester of pregnancy (from 11 + 0 to 13 + 6 gestational weeks). Unexpectedly, significantly lower E2 concentrations were detected in OD pregnancies compared to natural conception or autologous IVF pregnancies.…”
Section: The Early Stages Of Pregnancymentioning
confidence: 99%
See 2 more Smart Citations